Enrichment of CLDN18‐ARHGAP fusion gene in gastric cancers in young adults. Issue 4 (4th April 2019) - Nakayama, Izuma; Shinozaki, Eiji; Sakata, Seiji; Yamamoto, Noriko; Fujisaki, Junko; Muramatsu, Yusuke; Hirota, Toru; Takeuchi, Kengo; Takahashi, Shunji; Yamaguchi, Kensei; Noda, Tetsuo
Abstract : Gastric cancer in young adults has been pointed out to comprise a subgroup associated with distinctive clinicopathological features, including an equal gender distribution, advanced disease, and diffuse‐type histology. Comprehensive molecular analyses of gastric cancers have led to molecular‐based classifications and to specific and effective treatment options. The molecular traits of gastric cancers in young adults await investigations, which should provide a clue to explore therapeutic strategies. Here, we studied 146 gastric cancer patients diagnosed at the age of 40 years or younger at the Cancer Institute Hospital (Tokyo, Japan). Tumor specimens were examined for Helicobacter pylori infection, Epstein‐Barr virus positivity, and for the expression of mismatch repair genes to indicate microsatellite instability. Overexpression, gene amplifications, and rearrangements of 18 candidate driver genes were examined by immunohistochemistry and FISH. Although only a small number of cases were positive for Epstein‐Barr virus and microsatellite instability (n = 2 each), we repeatedly found tumors with gene fusion between a tight‐junction protein claudin, CLDN18, and a regulator of small G proteins, ARHGAP, in as many as 22 cases (15.1%), and RNA sequencing identified 2 novel types of the fusion. Notably, patients with the CLDN18‐ARHGAP fusion revealed associations between aggressive disease and poor prognosis, even when grouped by their clinical stage. These observations indicate that a fusion gene between CLDN18 and ARHGAP is enriched in younger age‐onset gastric cancers, and its presence could contribute to their aggressive characteristics. Abstract : In our gastric cancer in young adult cohort, we found enrichment of fusion genes between CLDN18 and ARHGAP . The positivity of the CLDN18‐ARHGAP fusion relates to advanced disease and poor prognosis, indicating its clinical relevance.